Comparing the Yield and Knowledge Level of Cluster Frontline Demonstration (CFLD) Beneficiaries and Non-Beneficiaries - Yadav, Rishabh; Singh, Lal Bahadur; Harsha; Singh, Shubham; Pandey, Mohit Kumar; Kumar, Manoj; Kumar, Ayush; C N, Amogh; Prajapati, Chandra Shekhar (Indian Journal of Extension Education, 2026)
The research was conducted during 2024-25, aimed to assess the benefits of the Cluster Frontline Demonstration (CFLD) programme on mustard cultivation knowledge and yield among farmers in Uttar Pradesh (UP). By employing the quasi-experimental design, comparing non-beneficiaries (B0), previous beneficiaries 2021–2024 (B1) and current beneficiaries 2024-25 (B2) with 120 participants each and a total sample size of 360, across three Krishi Vigyan Kendras (KVKs) of UP. The data was collected through a personal interview. Knowledge scores (% correct) and yield (q ha-1) were measured and compared by using Kruskal-Wallis and Mann-Whitney U tests. Results showed a significant difference in yield, i.e. 14.00 q ha-1 (B0) and 18.61 q ha-1(B2), and median knowledge increased significantly in variety (27.27% to 63.64%) and harvesting and threshing (50.00% to 100.00%) across three groups. All practices show a significant difference (p < 0.00625), with effect sizes up to 0.293. Results show that the CFLD programme significantly increases knowledge and yields, due to targeted training and resource support. Non-significant initial differences in some practices suggested overcoming barriers with sustained participation.